Renewable-energy education for mechanical engineering undergraduate students - Islam, Mazharul; Amin, M. Ruhul (Sage Publications, 2012)
Mechanical engineering (ME) encompasses a broad array of topics and subjects. A significant portion of renewable-energy technologies (RETs) can be directly or indirectly linked with different ME undergraduate courses or specializations. Gradually, the job markets for diverse fields of RETs are emerging for ME graduates. It will be beneficial for students to be well aware of the fundamentals of different RETs. This paper highlights the significance of different renewable sources of energy along with their contributions in the present global energy scenario. The diverse emerging modern technological options to harness these energy sources are discussed from an ME perspective. Finally, a model undergraduate ME course on the fundamentals of renewable energy is outlined.